Penerapan Metode Card Sort dalam Mengingkatkan Hasil Belajar Peserta Didik pada Mata Pelajaran Fikih Materi Bersuci Setelah Haid di Kelas IV MIN 5 Ciamis Tahun Pelajaran 2023-2024 - Sofi Sofiatin (Fisip UIN Sunan Gunung Djati Bandung, 2024)
This classroom action research aims to determine the application of the card sort method in improving student learning outcomes in the Fiqh subject material on purification after menstruation in class IV MIN 5 Ciamis in the 2023-2024 academic year and to determine the increase in student learning outcomes after applying the card sort method in Fiqh subject material on purification after menstruation in class IV MIN 5 Ciamis for the 2023-2024 academic year. This research was carried out at MIN 5 Ciamis using the Kurt Lewin model of classroom action research method which consists of three cycles, each cycle consisting of 4 stages, namely: planning, implementation, observation and reflection. The research population consisted of 51 students with a sample of 25 students. Research data was obtained by means of documentation studies, observations and tests, by testing the hypothesis that the indicator of success of this research is if the average score of students reaches more than 80%, experiencing learning completeness and performance indicators reach a score of more than 80 for the results of observing teacher activities and student activities. The results of this Classroom Action Research are that the application of the card sort method can improve student learning outcomes in the Islamic jurisprudence subject regarding purification after menstruation in class IV MIN 5 Ciamis for the 2023-2024 academic year. This is proven by the increase in student learning outcomes from 44% to 88% experiencing completeness in learning. Then the results of observations of teacher and student activities increased from 78 to 86. So by implementing the card sort method you can improve student learning outcomes.